How to Effectively Monitor and Evaluate NCD Programmes in India - Anand Krishnan; Vivek Gupta; Ritvik; Baridalyne Nongkynrih; J S Thakur (Wolters Kluwer Medknow Publications, 2011)
Program monitoring and evaluation (M and E) are important components of any program and are critical to sound strategic planning. The Ministry of Health and Family Welfare, Government of India, launched the National Programme for Prevention and Control of Cancer, Diabetes, Cardio-vascular diseases and Stroke (NPCDCS) with the objectives to prevent and control common noncommunicable diseases (NCDs) through behaviour and lifestyle changes, and to provide early diagnosis and management of common NCDs. M and E of program requires identification of indicators that measure inputs, process, outputs, and outcomes. The frequency of collecting information for these indicators will vary depending on the level of use and type of indicator as well as time interval over which we expect to see a change in that parameter. A group of indicators for different domains in the three major strategies has been proposed. For effective monitoring and evaluation of NPCDCS, the way forward is to finalize the list of indicators; evolve sustainable systems for surveillance; collect baseline assessment of the indicators at district level; fix targets for each indicator for different time frames; periodic review at state and national level for monitoring progress; and establish external review mechanisms. Monitoring and evaluation require complex set of co-ordinated action, responsibility for which has to be taken up by the NCD Cell within the Ministries of Health at state and national level. However, the routine data collection and compilation could be the responsibility of Central Bureau of Health Intelligence. Integrated population-based surveys with existing disease and behaviour surveillance could be undertaken by National Centre for Disease Control. The national NCD cell should compile all these information into a meaningful policy brief so that appropriate programmatic interventions can be identified. The launch of a national program to tackle the burden of NCDs is just the beginning, and the final success of the program will depend on how effectively we monitor and evaluate it.